If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -10 = -2(x + -1) Reorder the terms: -10 + y = -2(x + -1) Reorder the terms: -10 + y = -2(-1 + x) -10 + y = (-1 * -2 + x * -2) -10 + y = (2 + -2x) Solving -10 + y = 2 + -2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + y = 2 + 10 + -2x Combine like terms: -10 + 10 = 0 0 + y = 2 + 10 + -2x y = 2 + 10 + -2x Combine like terms: 2 + 10 = 12 y = 12 + -2x Simplifying y = 12 + -2x
| 6x+22=15x-68 | | 2(.5x-8)+9(x-3)=12 | | 5x^2-50x+45=0 | | 0.6g+11=15 | | 10+5x=54+x | | 2r^2-10r-100=0 | | .2(x-25.5)+.3=.2(x-16) | | 12(y-1)=3(2x-4) | | x^2+4x=6 | | 3y^3+9y^2-162y=0 | | 3y+5y=8 | | x+(x+2)+(x+4)=48 | | 3(y+1)=6 | | 6x+78=12x+12 | | 3y^3+9y^2-162x=0 | | (a^2+1)a^2-7(a^2+1)=0 | | 64-y=2y+6 | | 7x^2+35x-168=0 | | x^2-16x+58=0 | | 6x+6y=12 | | 6x+38=16x-52 | | x^2-16x+64=6 | | y+5=-(x-2) | | 12x^2+9=24x | | 5(d-45)=4(d-30)+10 | | 2x^3-10x^2-100x=0 | | 5(1-2w)+8=15 | | 92-34=42-9 | | 92-34=4z-9 | | 10x+7=8x-11 | | 6c^3-3c^2-45c=0 | | 3d^2-2d-33=0 |